2016
DOI: 10.1108/bfj-11-2015-0447
|View full text |Cite
|
Sign up to set email alerts
|

Consumer views on “healthier” processed meat

Abstract: /a> (2016),"Who cares for nutrition information at a restaurant? Food-related lifestyles and their association to nutrition information conscious behaviors",

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 46 publications
4
27
0
Order By: Relevance
“…Hemp seed and linseed are cheap and readily available materials, so adding them to a product such as pâté should not increase the final price, which is the most important factor when considering the overall impact on public health. The most important aspects to be considered when introducing a product such as this onto the market are the product's price and taste (Shan et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Hemp seed and linseed are cheap and readily available materials, so adding them to a product such as pâté should not increase the final price, which is the most important factor when considering the overall impact on public health. The most important aspects to be considered when introducing a product such as this onto the market are the product's price and taste (Shan et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…However, the presence of a claim is not always reflected in the intent to purchase the product. The credibility of both types of statements is comparable, although consumers rate the health claims slightly better than the nutritional claims [77].…”
Section: A Cegiełkamentioning
confidence: 93%
“…Shan et al. () investigated consumer attitudes towards functional processed meat and found that participants were uncomfortable with the idea of using processed meat as a carrier for healthy ingredients. In a later study, Shan et al.…”
Section: Consumer Preferences For Functional Foodmentioning
confidence: 99%
“…From their review they also note the importance of carrier to consumer uptake, identifying that the claimed benefits must be based on real evidence and that taste and convenience must not be compromised for the new functional product to be successful. Shan et al (2016) investigated consumer attitudes towards functional processed meat and found that participants were uncomfortable with the idea of using processed meat as a carrier for healthy ingredients. In a later study, Shan et al (2017) also identified that price, carrier (type of processed meat product), type of functional ingredient, and finally fat or salt content (in that order) were critical determinants of consumer intention to purchase a functional processed meat product.…”
Section: Consumer Preferences For Functional Foodmentioning
confidence: 99%
See 1 more Smart Citation